Acceptance of Islamic Banking in New Zealand: Perspectives from Potential Customers - Subramaniam, Geetha; Osman, Ismah; Muhamat, Amirul Afif; Ali, Ershad; Mohamad, Saadiah (Journal of Reviews on Global Economics, 2019)
The Islamic banking system stems from an interest free economic transaction model, which was introduced well in the early days of Islam. Even though the development of Islamic banking in the southern hemisphere is not as rapid as in the northern hemisphere, this does not imply that small western countries such as New Zealand are not interested in this niche sector. The increasing number of the Muslim population in New Zealand, which grew to 70,000 by 2018, shows that there may be a potential demand for Islamic financial services. This perception study which is part of a larger feasibility study uses a quantitative approach to examine the perception level of New Zealand residents towards their intention to use Islamic banking. Using purposive sampling technique, 300 questionnaires were distributed to potential banking customers, irrespective of religion, residing in New Zealand. Multiple regression analysis was conducted to capture whether the variables based on the theory of reasoned action including knowledge, religious values, subjective norms and attitude had an effect on the New Zealand residents' intention to use Islamic banking. It was interestingly noted that only attitude had a significant effect on how New Zealand residents perceive their intention to use Islamic banking in their daily lives. Overall, this study has ascertained the level of perception towards their intention to use Islamic banking among potential customers in New Zealand. The results of this study can be used as a framework for the setting up of an Islamic banking system in New Zealand.